2018
DOI: 10.1002/mc.22887
|View full text |Cite
|
Sign up to set email alerts
|

Dual use of hematopoietic and mesenchymal stem cells enhances engraftment and immune cell trafficking in an allogeneic humanized mouse model of head and neck cancer

Abstract: In this report, we describe in detail the evolving procedures to optimize humanized mouse cohort generation, including optimal conditioning, choice of lineage for engraftment, threshold for successful engraftment, HNSCC tumor implantation, and immune and stroma cell analyses. We developed a dual infusion protocol of human hematopoietic stem and progenitor cells (HSPCs) and mesenchymal stem cells (MSCs), leading to incremental human bone marrow engraftment, and exponential increase in mature peripheral human im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…More recently, researchers have determined that, whatever their other effects, injected MSCs do not alter the tumor immune response in HM 21 . In accordance with much of this data, we have shown that the isolation, coculture, and coinjection of cord blood–derived MSCs together with HSCs can produce HM with not only a higher percentage of human bone marrow cells but also with a greater percentage of circulating T and B cells, as well as monocytes 51 …”
Section: Engraftment Of Human Hematopoietic Tissuessupporting
confidence: 85%
See 3 more Smart Citations
“…More recently, researchers have determined that, whatever their other effects, injected MSCs do not alter the tumor immune response in HM 21 . In accordance with much of this data, we have shown that the isolation, coculture, and coinjection of cord blood–derived MSCs together with HSCs can produce HM with not only a higher percentage of human bone marrow cells but also with a greater percentage of circulating T and B cells, as well as monocytes 51 …”
Section: Engraftment Of Human Hematopoietic Tissuessupporting
confidence: 85%
“…Although several groups have reported tumor regression after administration of these agents, in many cases it is uncertain how this response compares to that of a patient 26,75 . We have observed tumor regression in response to nivolumab treatment, but only in very well‐humanized mice, and only using a PDX taken from a patient who was not treated with these immune checkpoint inhibitors 51 . When these HM contained even marginally less human bone marrow, we could not see this treatment effect.…”
Section: Therapeutic Use For the Hm Modelmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, the XactMice system accurately recapitulates the growth of the original tumor in vivo. The humanized mouse model of HNSCC was optimized in another study by Morton et al (163). After the dual infusion of human hematopoietic stem and progenitor cells (HSPCs) and mesenchymal stem cells (MSCs), the percentage of human immune cells in the bone marrow of established mice was almost twice that in mice implanted with HSPCs alone, and mature peripheral human immune cells were 9-38-fold more abundant.…”
Section: Humanized Mouse Modelsmentioning
confidence: 99%